Active K‐RAS induces the coherent rotation of epithelial cells: A model for collective cell invasion in vitro - Hirata, Eishu; Ichikawa, Takehiko; Horike, Shin‐ichi; Kiyokawa, Etsuko (Cancer science, 2018)
At the invasive front of adenocarcinomas, single cells and multicellular structures exist; the latter include glands and cell clusters, such as tumor buddings and poorly differentiated clusters. Recent reports suggest the importance of collective cell migration in metastasis; however, it is technically difficult to observe the movement of multicellular structures in vivo. We utilized MDCK cells as a model for epithelial cells and established a method to quantify their motility in 3D structures in vitro. A single MDCK cell grows as a cell cluster in the gel and later proliferates and forms a cyst. Active K‐RAS expression induced rotation of both the cell clusters and the cysts. The rotation speed of cell clusters was 4 times higher than that of cysts. The screening of inhibitors for their effects on cell clusters and cysts revealed that cyclin B1 and β‐catenin were the key molecules for their rotation, respectively. Regulators for cyst rotation, such as vorinostat and β‐catenin, were not effective for inducing cell cluster rotation. These results indicate that the signaling pathways of cell dynamics are different between cell clusters and cysts. As cell clusters are related to lymph node involvement and the prognosis of various carcinomas, our in vitro quantitative system may be useful for the screening of drugs to prevent lymphatic invasion. At the invasive front of adenocarcinomas, single cells and multicellular structures exist; the latter include glands and cell clusters. Using in vitro quantification methods, we found that the signaling pathways of cell dynamics are different between cell clusters and cysts (glands).